Chinese Creative Writing Studies - Rebecca Leung, Mo-Ling. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book introduces Chinese creative writing to the English-speaking world, considering various aspects of literary and creative theories in research in Chinese writing. It covers recent trends such as cross-media practices, pedagogy in creative writing in China, Taiwan and Hong Kong, specifically, and looks at how Chinese classical culture brings new interpretations to creative writing within a global context. Consisting of 14 chapters by established scholars and experts, writers, and poets working in various genres within the Chinese writing tradition, the book presents data accrued from personal reflections, classroom teaching, video games, museum studies, radio dramas, TV series, and cyber-literature. The book includes leading Chinese leading scholars' reflections on research and the field, providing an omnibus perspective on theories of creative writing. It focuses on the interconnection between Chinese creative writing and pedagogy and examines different writer-training methods in Mainland China, Hong Kong, and Taiwan, offering a comparative perspective that deepens the understanding of institutional effects on the development of creative writing. It unpacks the interaction between Chinese creative writing and multimedia and ascertains the possibilities of incorporating media studies into writing practices. It also presents new interpretations of Chinese classical culture assets to new creative or literary manuscripts, such as TV series adaptation and Internet literature. Relevant to researchers, teachers, and students working Chinese creative writing and Chinese literature, it is also a landmark text in exposing English-speaking creative writing scholars to the wealth of Chinese creative writing, in English.
Part 1. Part I Creative Writing Theories and Research in Chinese Context -- Chapter 1. Therapeutic Writing: As the Opposite of Creative Writing -- Chapter 2. 2020 Annual Report of China's Creative Writing Studies -- Part 2. Teaching Creative Writing in China, Taiwan and Hong Kong -- Chapter 3. Radio Drama Creation and the Development and Training of Related Indus-tries -- Chapter 4. A Discussion on the Teaching of Creative Writing in the Writing Classes of Universities in China -- Chapter 5. Basic Teaching of Creative Writing as a "Pool of Inspiration": A Discussion Starting from the Undergraduate Teaching of Drama and Film Arts in the Creative Writing Programme -- Part 3. Creative Writing and Cross-Media Practices from the Sinophone Perspective -- Chapter 6. Reading for Writing: A Case Study of Cross-Media Reading Achievements -- Chapter 7. Creative Writing in the Narratives of Interactive Games - The Cases of Grand Theft Auto 5 and The Witcher 3: Wild Hunt -- Chapter 8. A Preliminary Study of Transmedia Storytelling: Taking a Special Exhibition of the Hong Kong Heritage Museum as an Example -- Part 4. Creative Writing and New Interpretations of Chinese Classical Culture -- Chapter 9. A Discussion on "Southeast Fly the Peacocks" and Its TV Series Adaptation from the Perspectives of "Chinese Tragic Consciousness" and "Intertextual-ity" -- Chapter 10. Resources for Creativity from Chinese Classical Culture: A Discussion on the Creative Thinking and Creation Pattern of "Old Tales Retold" and its Reve-lations on the Development of Creative Writing -- Chapter 11. The "First Generation" of Creative Cyber Literature and its "Genre-Bending Writing": Thoughts on Using Jun Tian as a Method -- Part 5. Implications of Global Contexts for Creative Writing -- Chapter 12. Creative Writing Research: What, How and Why -- Chapter 13. In Praise of Doggedness: On-Going Local & Becoming Global as Transpacif-ic Poet-Scholar in Hawai'i, Pacific Rim, Coastal California -- Chapter 14. Toward a Unified Field: Lore and the Complications of Global Context.
Keywords: Creative writing; Oriental literature; Interpretation, Literary; Literature; Teaching; Mass media and culture; Creative Writing; Asian Literature; Literary Interpretation; Literary Methods; Pedagogy; Media Culture